The Role Of Cyberchondria In Mediating Health Anxiety, Fears And Obsessions Among Students Of Private Medical Colleges Sargodha - Muhammad Usman; Adnan Afzal; Muhammad Afzal; Sundas Ahmad; Bilal Habib; Amina Iqbal (Journal of Rawalpindi Medical College)
Objective: This study was conducted to examine the role of cyberchondria in mediating health anxiety, fears and obsessions among Students of private medical college.